Educational Services for Slow Learners by Motivational Teachers in Elementary Schools - Choiriyah Widyastuti (Institut Studi Islam Muhammadiyah Pacitan, 2025)
Students with special needs who are slow learners are students who have slower learning abilities than other students, characterized by difficulties in learning and understanding academic and skill-related information, low academic achievement, frequent tardiness in submitting assignments, and requiring a long time to understand lesson material. This study uses a qualitative descriptive approach with a phenomenological research type that will describe the process of learning implementation by Motivational Teachers. The data collection techniques used in this study are interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, verification, and conclusion drawing. The aspects studied are the strategies used by Motivational Teachers in providing services to slow learners as a form of tutoring during the learning process, as seen from the provision of assistance in the form of accommodation services in teaching methods and materials, assignments and assessments, time requirements, and the learning environment. The results of the study show that the services provided by Motivational Teachers for slow learners in elementary schools in Sukoharjo Regency cover three aspects, namely modification of time allocation, modification of content or material, and modification of the learning process. In addition, the use of media in the learning process was also found. The services provided by Motivational Teachers have been implemented well.